PENGARUH SUPERVISI AKADEMIK KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU SMP NEGERI SEKECAMATAN TAMALATEA KABUPATEN JENEPONTO - Trisnawati H; Abdul Saman; Hasan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to (1) provide an overview of the school principal's academic supervision in Public Junior High Schools in Tamalatea District; (2) provide an overview of teachers' work motivation in Public Junior High Schools in Tamalatea District; (3) provide an overview of teachers' performance in Public Junior High Schools in Tamalatea District; (4) analyze the influence of the school principal's academic supervision on the performance of teachers in Public Junior High Schools in Tamalatea District; (5) analyze the influence of work motivation on the performance of teachers in Public Junior High Schools in Tamalatea District; (6) analyze the combined influence of academic supervision and work motivation on the performance of teachers in Public Junior High Schools in Tamalatea District. This research employs a quantitative method with a correlational research design. The study was conducted at five schools in Tamalatea District, Jeneponto Regency, namely UPT SMP Negeri 1 Tamalatea, UPT SMP Negeri 2, UPT SMP Negeri 3, UPT SMP Negeri 4 Tamalatea, and UPT SMP Negeri 5. The results show that: The school principal's academic supervision in Public Junior High Schools in Tamalatea District is rated very good by teachers and has a positive impact on their performance. Teachers' work motivation is also high, with slight variation, indicating a supportive professional development environment. Teachers' performance is in the good category, although some teachers are in the moderate and low categories. Academic supervision and work motivation play a significant role in improving the quality of teachers' performance. Academic supervision contributes 29.2% to teachers' performance, while work motivation contributes 47.9%. Multiple regression analysis shows that academic supervision and work motivation together have a significant influence of 49.7% on teachers' performance.